La conquête chrétienne d’Ejea à travers l’intervention de guerriers gascons et d’un saint girondin - Alexandre Giunta (Bulletin du Centre d’Études Médiévales d’Auxerre)
At the end of the 11th Century, Christians tried to snatch Ejea from the Muslims without success. But in 1105 the followers of Islam could not withstand the pressure of Alfonso I El Batallador. The town became part of the medieval Kingdom of Aragon. By tradition, many nobles and knights noted for their skill at arms from France and beyond the passes of the Pyrenees had joined Alfonso I. They asked him that the churches that might be built at Ejea be dedicated to the work of French monastery of Sauve Majeure. After the conquest, a group of monks settled down in the city where they had privileges and administered the sacraments to the people of the region. In this article, we shall analyze the conditions of this conquest and the role of the French knights through some chronicles and charts.